Positional and temporal differences in peak match running demands of elite football - Thoseby, Bradley; D. Govus, Andrew; Clarke, Anthea; J. Middleton, Kane; Dascombe, Ben (Biology of Sport, 2023)
Temporal changes in the total running demands of professional football competition have been well documented, with absolute running demands decreasing in the second half. However, it is unclear whether the peak match running demands demonstrate a similar decline. A total of 508 GPS files were collected from 44 players, across 68 matches of the Australian A-League. GPS files were split into the 1st and 2nd half, with the peak running demands of each half quantified across 10 moving average durations (1–10 min) for three measures of running performance (total distance, high-speed distance [> 19.8 km·h −1 ] and average acceleration). Players were categorised based on positional groups: attacking midfielder (AM), central defender (CD), defensive midfielder (DM), striker (STR), wide defender (WD) and winger (WNG). Linear mixed models and effect sizes were used to identify differences between positional groups and halves. Peak running demands were lower in the second half for STR across all three reported metrics (ES = 0.60–0.84), with peak average acceleration lower in the second half for DM, WD and WNG (ES = 0.60–0.70). Irrespective of match half, AM covered greater peak total distances than CD, STR, WD and WIN (ES = 0.60–2.08). Peak high-speed distances were greater across both halves for WIN than CD, DM and STR (ES = 0.78–1.61). Finally, STR had lower peak average acceleration than all positional groups across both halves (ES = 0.60–1.12). These results may help evaluate implemented strategies that attempt to mitigate reductions in second half running performance and inform position specific training practices.